Spatial and temporal variability in Acacia population dynamics - Staver, A Carla (Department of Biological Sciences, 2024)
Variability in fire, herbivory, and climate facilitate the coexistence of trees and grasses in savannas and impact upon savanna structure, which also varies substantially both spatially and temporally. These features can shape savannas at an ecosystem and even at a global scale, but mechanisms for the effects of fire, herbivory, and climate variability on tree cover are often demographic at the tree population level. Sapling growth in particular has repeatedly been shown to be the limiting step, or 'bottleneck', in the establishment of trees in savannas. I set out to investigate how spatial and temporal variability in fire, herbivory, and climate shape population dynamics of a suite of common African savanna trees, the Acacia, in a landscape context. I carried out my field work in Hluhluwe iMfo lozi Park in KwaZulu Natal, South Africa, during 2006 and 2007. Fire, herbivory, and the grass layer were primary determinants of distributions and co-occurrence of Acacia species. They primarily affected saplings, indicating that sapling survival may determine distributions of adults. Moreover, communities were structured by species' direct interactions with fire and herbivory, rather than by competitive interactions with each other. Spatial heterogeneity in fire and herbivory resulted in an ecologically diverse suite of Acacia species. Even within the environments in which different species occurred, both fire and herbivory had the ability to directly suppress Acacia sapling growth and limit establishment of adult trees. Sapling growth and maturation, rather than seedling establishment or sapling mortality, appeared to be the limiting step. A herbivore exclusion experiment showed that at mesic sites, where growth rates were higher, browsing and fire acted together to limit sapling growth, while at semi-arid sites, ii browsing or fire alone was sufficient to prevent saplings growmg. Reductions in browsing resulted in increases in sapling growth, indicating that variability in herbivore pressure impacts adult establishment and tree population dynamics. A long-term study of establishment of Acacia trees using age estimation of adults via dendrochronology indicated that tree recruitment is not continuous at local or landscape scales. A. karroo recruitment occurred within the last 20 years during periods without fire on a local scale; however, on a landscape scale, decreases in fire frequency were linked to periods of drought. I was unable to link recruitment of A. nilotica and A. nigrescens directly to climate, fire or herbivore population records, but recruitment of both species appeared to have stopped in the 1970s. In mesic areas, dominance seemed to be shifting from A. nilotica to A. karroo, while in semi-arid areas, large A. nigrescens trees are not being replaced. This suggests that major shifts in species dominance and even savanna structure are characteristic of these savannas. Savannas are highly variable systems that are not adequately described by equilibrium ecology models. Non-equilibrium dynamics must form a more fundamental part both of theoretical savanna ecology and of savanna management.